A CRITICAL REVIEW OF THE RELEVANCE OF KARL MARX’S THOUGHT IN INTERPRETING STRUCTURAL INEQUALITY IN CONTEMPORARY INDONESIA - Fatah, Rahmat Abd (International Journal of Multidisciplinary Reseach, 2026)
This article offers a critical review of Karl Marx’s contribution to understanding contemporary social realities in Indonesia, particularly in relation to structural inequality generated by global capitalism. The author examines key Marxian concepts such as class conflict, alienation, ideology, and false consciousness, while critically assessing both their limitations and their practical applicability within the local context. Employing a qualitative approach and thematic analysis of recent literature, the article emphasizes the importance of rereading Marx in order to develop a theoretical framework that is not only critical but also context-sensitive. It argues that Marx’s thought remains relevant, yet requires reinterpretation that is attentive to Indonesia’s socio-political dynamics.